DAMPAK COVID-19 BAGI RODA PEREKONOMIAN BAGI MASYARAKAT INDONESIA - Cici Widya Prasetyandari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2021)
Coronavirus (Covid-19) is a large family of viruses that cause disease in humans and animals. This virus has rocked the world throughout 2020. The purpose of this research determine the impact of Covid-19 on the Indonesian economy. The research method used is qualitative research and literature study. The results of this study indicate that the impact felt by the Indonesian people related to the economy is felt by various groups, such as online motorcycle taxis, traders, artists and entrepreneurs. Covid-19 forces people to survive amid the current economic difficulties. The efforts made by the government to alleviate poverty due to the Covid-19 pandemic are by providing social assistance to the community, holding pre-employment cards, subsidizing 100% electricity with 450 Watt power, and providing subsidies for small business.